The Effects Of Foreign Trade, And Volatility Of Exchange Rate On Economic Growth In Sub-Saharan African Countries - Safiyanu, Shuaibu Sidi (2021)
This study investigates the effects of foreign trade, volatility of exchange rate on economic growth in a panel sample of 40 sub-Saharan African (SSA) countries over the period of 1992-2018 using Augmented Mean Group (AMG) along with Dynamic Common Correlated Effects (DCCE) estimators. Firstly, it examines the relationship between foreign trade and economic growth in SSA countries. Secondly, the study investigates the effects of exchange rate volatility on trade. Thirdly, the study examines whether the effects of foreign trade on economic growth volatility vary with the degree of export concentration in SSA countries.